2017
DOI: 10.12693/aphyspola.132.469
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cyclohexene with H2O_2 Catalyzed by Vanadium Based Polyoxometalates Doped Modified Clays as Green Catalysts

Abstract: The catalytic performance of supported heteropolyacids in various liquid-solid and gas-solid heterogeneous reactions may be affected by the choice of support and/or the method of heteropolyacid deposition. Vanadium substituted polyphosphomolybdate with the Keggin structure H4[PVMo11O40]·13H2O (PVMo) was dispersed throughout acid activated bentonite (clay from Hammam Boughrara, Maghnia, Algeria). A series of catalysts were prepared via modified impregnation. Modified preparation method employed ultrasonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…S1). These bands result in the interaction of P with O and Mo with O, respectively, whereby the interaction of Mo and O leads to three distinguishable bands, depending on the position of the oxygen within the Keggin structure .…”
Section: Resultsmentioning
confidence: 99%
“…S1). These bands result in the interaction of P with O and Mo with O, respectively, whereby the interaction of Mo and O leads to three distinguishable bands, depending on the position of the oxygen within the Keggin structure .…”
Section: Resultsmentioning
confidence: 99%
“…Absorption bands described in the literature for HPA-5 also appear in the IR spectrum. These bands result in the interaction of P with O and Mo with O, respectively, whereby the interaction of Mo and O leads to three distinguishable bands depending on the position of the oxygen within the Keggin structure. , The FTIR spectra were recorded in KBr discs using a Jasco FT/IR-4100 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Three major products cyclohexenol, cyclohexenone and cyclohexene oxide were obtained with 49% conversion in 7 h. PVMo/Hmont has been reported for allylic oxidation with hydrogen peroxide. Cyclohexene oxide, cyclohexenol, cyclohexenone and cyclohexanol were produced where the conversion was 98% [8]. Junghans et al [9] has reported Copper-MOF (metal-organic framework) with triazolyl isopthalate linkers for oxidation of cyclohexene where the three major products were obtained with tertiary butyl hydroperoxide (TBHP) after 7 h. Farzaneh et al [10] reported Mn-MOF with benzenetricarboxylate (BTC) and dimethylfurane (DMF) for oxidation of different alkanes and alkenes in the presence of TBHP.…”
Section: Introductionmentioning
confidence: 99%